PENERAPAN PEMBELAJARAN SOCIAL EMOTIONAL LEARNING (SEL) DALAM PEMBENTUKAN KARAKTER ISLAMI PADA ANAK USIA DINI - Qori Dalimunthe, Amsal; Nurcahyati Sinulingga, Neng; Mariati, Mariati; Dedi Chandra, Muhammad; Syaifani, M.Irfan (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to examine the application of social emotional learning (SEL) integrated with Islamic character values in early childhood education. This study uses a qualitative approach with a literature review research design, examining literature from the fields of Islamic education and child development psychology. The focus of the study is on the synchronization of the five domains of SEL competencies self-awareness, self-management, social awareness, relationship skills, and decision-makingÃ¢â‚¬â€with Islamic values such as honesty, patience, gratitude, responsibility, etiquette, empathy, and monotheism. The findings of this study indicate that (1) Social and Emotional Learning (SEL) plays a crucial role in shaping the character foundation of children from an early age, (2) Islamic values such as honesty, patience, responsibility, and spirituality can be fully integrated into each domain of SEL competencies, (3) The success of implementation is greatly influenced by teacher role modeling, family involvement, and consistent environmental support; however, it still faces serious challenges such as insufficient professional training and high exposure to uncontrolled digital technology. (4) Concrete implementation practices can be realized through structured activities such as circle time, storytelling about the Prophet, role-playing, collaborative projects, and daily worship routines.